2021
DOI: 10.48048/tis.2021.29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combining Maize Straw and Palm Oil Fuel Ashes in Concrete as Partial Cement Replacement in Compression

Abstract: The high energy consumption connected with cement manufacturing, as well as the depletion of limestone resources and the release of carbon dioxide, which contributes to global warming, are all important issues that must be addressed. Partially replacing cement with agricultural wastes in concrete, which reduces cement output, is an innovative solution to this problem. This paper examined the effect of combining Palm Oil Fuel Ash (POFA) and Maize Straw Ash (MSA) as partial replacement of cement on the compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…About 70% of the raw materials from which palm oil is produced result in waste [22]. POFA is generated from the calcination of some components of palm trees such as palm oil fibre, palm kernel shells, and palm oil husk, which are considered wastes and often dumped in open spaces generating environmental pollution leading to health hazards [35]. However, several research findings such as that of Thomas et al [50], Sanawung et al [42] and Pone et al [40] have revealed that POFA possesses high pozzolanic properties just like silica fume and thus can be used as a replacement for cement for construction purposes.…”
Section: Introductionmentioning
confidence: 99%
“…About 70% of the raw materials from which palm oil is produced result in waste [22]. POFA is generated from the calcination of some components of palm trees such as palm oil fibre, palm kernel shells, and palm oil husk, which are considered wastes and often dumped in open spaces generating environmental pollution leading to health hazards [35]. However, several research findings such as that of Thomas et al [50], Sanawung et al [42] and Pone et al [40] have revealed that POFA possesses high pozzolanic properties just like silica fume and thus can be used as a replacement for cement for construction purposes.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the coal gangue particles are tightly packed and the reaction products (CSH and ettringite) are denser and more durable. Odeyemi et al (2021) noted that there was a progressive increase in the compressive strength of concrete molded with a blend of corn straw ash and Palm Oil Fuel Ash (POFA) as the curing days increased. The optimal combination of ash percentages for replacing cement was found to be 30% POFA and 16.6% CSA.…”
Section: Paste Compressive Strengthmentioning
confidence: 99%
“…It can be observed that, similar to CSA, the utilization of RHA did not result in a significant increase in water absorption. Even so, it is noteworthy that there is an increase in water absorption with the addition of corn stover ash, as well as a decrease in density as corn stover ash increases (Odeyemi et al, 2021;Opeyemi;Otuaga;Oluwasegunfunmi, 2014;Raheem et al, 2017).…”
Section: Paste Compressive Strengthmentioning
confidence: 99%
“…Cement, being one of the fundamental constituents in concrete production, causes a grave hazard by emitting carbon dioxide, and other greenhouse gases into the environment at an alarming rate, which are largely responsible for global warming. It was estimated that about 0.9 tons of carbon dioxide is released into the environment when producing a ton of cement [5,6]. Over the years, researchers have suggested different industrial by-products and agricultural residues as alternative binders in the production of durable and sustainable concrete [7,8].…”
Section: Introductionmentioning
confidence: 99%